Screening items in an aging chain with a co-flow structure: an application to the product pipeline management problem - Figueiredo, Paulo (2014)
In many situations, System Dynamics modelers have to capture attributes of items that are tracked in an aging chain. The outflow of items from the stocks in these chains usually depends on the attributes that are tracked in the co-flow. But these well known, classic models fail to account for a specific phenomenon, the screening of items. This study presents a new application of co-flows in aging chains: A co-flow that enables the process of screening, i.e. the process of either terminating or approving items depending on an attribute. Many possible applications are suggested. An application to product pipeline management is developed.